Insights into TIM‐Barrel Prenyl Transferase Mechanisms: Crystal Structures of PcrB from Bacillus subtilis and Staphylococcus aureus. Issue 2 (15th January 2013) - Ren, Feifei; Feng, Xinxin; Ko, Tzu‐Ping; Huang, Chun‐Hsiang; Hu, Yumei; Chan, Hsiu‐Chien; Liu, Yi‐Liang; Wang, Ke; Chen, Chun‐Chi; Pang, Xuefei; He, Miao; Li, Yujie; et al.
<x xml:space="preserve">Abstract</x> Well structured: As a new triose phosphate isomerase (TIM) barrel‐fold prenyl transferase, PcrB catalyzes the production of heptaprenylglyceryl phosphate from heptaprenyl diphosphate and glycerol‐1‐phosphate. Crystal structures of PcrB from Bacillus subtilis and Staphylococcus aureus in complex with ligands were solved, and together with site‐directed mutagenesis and bioinformatics analyses, clearly reveal the catalytic mechanism of the enzyme.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>